Electricity generation from organic fraction of municipal solid wastes in tubular microbial fuel cell - Karluvali, Arda; Koroglu, Emre O.; Manav, Neslihan; Cetinkaya, Afsin Y.; Ozkaya, Bestami (ELSEVIER, 2015)
Microbial fuel cell (MFC) has the potential to be an alternative pretreatment method to divert organic fraction of municipal solid waste (OFMWS) from landfilling while sustainable, clean and renewable energy can be obtained during organic matter removal. Thus searching for optimal conditions to achieve more energy and organic removal is critical for the practical application of MFCs. Herein, an approach investigating the temperature effect on reactor performance and waste treatment was adopted to address the question using a tubular MFC. In this study, MFC was operated in fed-batch mode and the reactor temperature was gradually increased with 5 degrees increments at mesophilic range from 20 degrees C to 35 degrees C. Due to temperature rise, maximum current density Increased from 197.7 mA/m(2) to 355.4 mA/m(2) and maximum power density production tripled from 14.8 mW/m(2) to 47.6 mW/m(2) at 100 Omega external resistor. Unlike current and power yield, coulombic efficiency (CE) and soluble chemical oxygen demand (SCOD) removal efficiency followed a slightly escalating trend with temperature rise in mesophilic range. Based on 16S rRNA sequence analysis, the bacterial strain were identified as Geobacter, which play an important role in transferring electrons to the electrodes, and also Bacteroides and Clostridium, which contribute to fermentation. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Microbial fuel cell; Municipal solid waste; Temperature; Tubular Nafion; POWER-GENERATION; BACTERIAL COMMUNITIES; PERFORMANCE; WATER; DYNAMICS; ANODE; MFC; DIVERSITY; MEMBRANE; Engineering